Drivers for the artisanal fisheries production in the Magdalena River - Jiménez-Segura, Luz; Restrepo-Ángel, Juan D.; Hernandez-Serna, Andrés (Frontiers in Environmental Science, 2022)
We review knowledge on the Magdalena River in Colombia and its fish to identify those drivers that influence the artisanal fisheries production. We identify eight direct drivers (four natural and four anthropogenic) and at least four indirect drivers. Those drivers modify conditions in the fluvial network that promote fish movements, reproduction, and their larvae survivor. Landscape, rains, floods, connectivity of the fluvial net as land cover change, water pollution, hydropower, and alien species are the natural and anthropogenic direct drivers described in this article. The river–lake interaction dynamics in the Magdalena River are determined by two rainy cycles per year. Two seasonal flooding periods induce two cycles in the biological productivity of floodplains because water and sediment inputs. The most visible consequences in these hydrological cycles are the migrations of potamodromous fish and the periodic increase in the artisanal fishery production. Major floodplains are reducing their storage capacity by trapping ∼10%–40% of upstream sediment production. This process induces many research questions about rates of biomass production, carbon fluxes in the basin, impacts of human-induced erosion, and increasing rates of sediment load on floodplain connectivity, but still there is not enough data to answer them. Finally, we make some suggestions toward the sustainability of the Magdalena floodplains. The well-being of the floodplain ecosystems and their connectivity with the main river are the main tools to preserve and manage the ecosystem services of the Magdalena River and its floodplains lakes.